Identification and preliminary validation of biomarkers associated with mitochondrial and programmed cell death in pre-eclampsia - Lin, Rong; Weng, XiaoYing; Lin, Liang; Hu, XuYang; Liu, ZhiYan; Zheng, Jing; Shen, FenFang; Li, Rui (Frontiers in Immunology, 2025)
BackgroundThe involvement of mitochondrial and programmed cell death (mtPCD)–related genes in the pathogenesis of pre-eclampsia (PE) remains inadequately characterized.MethodsThis study explores the role of mtPCD genes in PE through bioinformatics and experimental approaches. Differentially expressed mtPCD genes were identified as potential biomarkers from the GSE10588 and GSE98224 datasets and subsequently validated. Hub genes were determined using support vector machine, least absolute shrinkage and selection operator, and Boruta based on consistent expression profiles. Their performance was assessed through nomogram and artificial neural network models. Biomarkers were subjected to localization, functional annotation, regulatory network analysis, and drug prediction. Clinical validation was conducted via real-time quantitative polymerase chain reaction (RT-qPCR), immunofluorescence, and Western blot.ResultsFour genes [solute carrier family 25 member 5 (SLC25A5), acyl-CoA synthetase family member 2 (ACSF2), mitochondrial fission factor (MFF), and phorbol-12-myristate-13-acetate–induced protein 1 (PMAIP1)] were identified as biomarkers distinguishing PE from normal controls. Functional analysis indicated their involvement in various biological pathways. Immune analysis revealed associations between biomarkers and immune cell activity. A regulatory network was informed by biomarker expression and database predictions, in which KCNQ1OT1 modulates ACSF2 expression via hsa-miR-200b-3p. Drug predictions, including clodronic acid, were also proposed. Immunofluorescence, RT-qPCR, and Western blot confirmed reduced expression of SLC25A5, MFF, and PMAIP1 in PE, whereas ACSF2 was significantly upregulated.ConclusionThese four mtPCD-related biomarkers may play a pivotal role in PE pathogenesis, offering new perspectives on the disease’s diagnostic and mechanistic pathways.